Evaluation De La Production De Cinq Genotypes De Palmier A Huile (Elaeis Guinnensis Jacq.) Replantes Sur Des Parcelles A Haute Densite De Fusariose - Allou, Désiré; Kouakou, Kouadio Olivier; Sekou, Diabaté; Nguetta, Assanvo Simon-Pierre (European Scientific Journal, ESJ, 2017)
Fusarium wilt is the most serious disease of the oil palm (Elaeis guineensis Jacq.) In Africa. The methods of fighting this disease are mainly based on the search for tolerant plant material, so the researchers of CNRA were able to make available to the producers of the genotypes tolerant to the Fusarium wilt. However, two of these supposedly tolerant genotypes, planted on plot D9-3 in Ehania, a highly endemic plot, showed symptoms of vascular Fusarium wilt after 9 years of replanting. The evaluation of production responses in comparison with the physiological states of other genotypes of the same parental origin showed that the LM25373 and LM25635 progenies retained their ability to produce in spite of their doubtful physiological state. The appearance of the external symptoms of FHB did not affect the cycles of production of these so-called diseased progeny.